Exploration of Capturing CO2 from Flue Gas by Calcite Slit‐Nanopores: A Computational Investigation. Issue 9 (10th August 2018) - Sun, Haoyang; Zhao, Hui; Qi, Na; Zhang, Xiaohan; Li, Ying
Abstract: Capturing CO2 from flue gas is recognized as a key process to improve the environment, therefore, developing a new cost‐effective sorbent is crucial. In this study, the calcite slit‐nanopores with various pore sizes ranging from ∼5 Å to ∼30 Å were constructed, the grand canonical Monte Carlo (GCMC) and molecular dynamics (MD) simulation methods were used to examine the microscopic behaviors of CO2 and N2 in calcite slit‐nanopores. Diverse adsorption layer structures for CO2 and N2 molecules as single component in calcite slit‐nanopores are found as the pore size changing, of which the CO2 represents a transformation from single adsorption layer to five adsorption layers, while N2 represents a variation from single adsorption layer to three adsorption layers. Meantime, different adsorption orientations of CO2 and N2 molecules adsorbed close onto the calcite pore surface are also found. Moreover, strong competitive adsorption of CO2 over N2 is found due to the different interactions between CO2 and N2 molecules with the calcite pore surface, the capacity of competitive adsorption decreases with the pore size increasing. The self‐diffusion and isosteric heat of CO2 and N2 molecules in calcite slit‐nanopores are also examined to demonstrate the different adsorption intensities of gases in calcite slit‐nanopores. This work demonstrates the detailed microscopic behaviors of CO2 and N2 molecules in calcite slit‐nanopores, which not only enriches the theoretical knowledge about gases adsorption in calcite slit‐nanopores, but also gives out the feasibility of capturing CO2 from flue gas by calcite‐based substances. Abstract : Strong competitive adsorption of CO2 over N2 occurred in calcite slit‐nanopores.